Sindbis Virus Replication Reduces Dependence on Mitochondrial Metabolism During Infection - Rodriguez, Juan L.; Costlow, Jessica L.; Sheedy, Max; Yoon, Kelly T.; Gabaldón, Annette M.; Steel, J. Jordan (Frontiers in Cellular and Infection Microbiology, 2022)
Alphaviruses are single stranded, positive sense RNA viruses that are often transmitted through mosquito vectors. With the increasing spread of mosquito populations throughout the world, these arboviruses represent a significant global health concern. Viruses such as Sindbis Virus (SINV), Chikungunya Virus (CHIKV) and Equine Encephalitis Viruses (EEV) are all alphaviruses. As viruses, these pathogens are dependent on the host cell environment for successful viral replication. It has been observed that viruses manipulate cellular metabolism and mitochondrial shape, activity, and dynamics to favor viral infection. This report looked to understand the metabolic changes present during Sindbis virus infection of hamster and human kidney cells. Cells were infected with increasing levels of SINV and at 24 hours post infection the mitochondria morphology was assessed with staining and mitochondrial activity was measured with a real-time Seahorse Bioanalyzer. The relative amount of mitochondrial staining intensity decreased with Sindbis virus infected cells. . Both oxygen consumption rate and ATP production were decreased during SINV infection while non-mitochondrial respiration and extracellular acidification rate increased during infection. Collectively, the data indicates that SINV primarily utilizes non-mitochondrial metabolism to support viral infection within the first 24 hours. This understanding of viral preference for host cell metabolism may provide critical targets for antiviral therapies and help further define the nature of alphavirus infection.